A current state of metal additive manufacturing methods: A review. (2022) - Durai Murugan, P.; Vijayananth, S.; Natarajan, M.P.; Jayabalakrishnan, D.; Arul, K.; Jayaseelan, V.; Elanchezhian, J.
Abstract: Alloys such as super alloys, Aluminium, titanium alloys are employed for metal additive manufacturing significantly. These alloys are used to make aircraft components, gas turbines and other structural areas. Additive manufacturing (AM), is also known as direct digital manufacturing methods, has improved the mechanical properties of additively manufactured metals. This paper overviews about various metal additive manufacturing methods on recent development and impact of process factors on mechanical behaviour, microstructures, formation of voids, surface status and appearance with respect to various additively manufactured metal alloys. In addition, this article reviewed about the printing challenges pertaining to cracks and void formation, behaviour of material, merits and limitations and layer by layer printed material appearance. Overall, this article gives an overview of metal additive manufacturing, including its benefits and limitations as a criterion for further research in additive manufacturing.